KOMUNIKASI PARTISIPATIF UNTUK MENGATASI PENOLAKAN PEDAGANG TERHADAP REVITALIASASI PASAR - Edhy Aruman, Akhmad (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2023)
This research originated from the delays in the Bogor traditional market revitalization plan due to resistance by traders. The purpose of this study is to explain the causes and forms of traders' resistance to the revitalization plan. This research uses a critical constructivist approach based on James C Scott's concept of resistance. Weak environmental support, entrepreneurial capacity, and participatory communication make traders marginalized from their environment which in turn raises traders' resistance actions both individually and in groups. The weak position of traders on the one hand and the dependence of traders on the market as a place of livelihood, has forced the resistance to be carried out peacefully through an alliance of traders, media and legal practitioners to gain public support. Through the association, traders reject the revitalization plan through legal channels. Individual traders refuse by delaying or refusing to pay the monthly levy. The goal to be achieved from the resistance is not to change the revitalization policy but rather to struggle so that market managers accommodate the interests of traders, namely occupying the same location as the market before it was revitalized